IMPLEMENTASI MODEL PEMBELAJARAN PBL BERBASIS METAKOGNISI UNTUK MENINGKATAN KEMAMPUAN PROBLEM SOLVING SANTRI SULTHONIYAH SAMBAS - Asyura, Muhammad; Mutazam, Mutazam (Borneo : Journal of Islamic Studies, 2023)
The aim of this research is to improve Santri’s ability to solve mathematical problems with problem-based learning (PBL) and structured metacognition. This type of research is an experimental study. In the class, treatment was given by applying the PBL method, with the number of respondents as high as 32 santriwati. The results of the data analysis obtained were: (1) Santri's initial ability to solve problems before treatment was still low; (2) there was a significant improvement between the initial ability of the center in problem solving and after treatment; and (3) there was an improvement in problem-solving ability in the class that applied metacognitive structured PBL. 4) The level of contribution given to learning with PBL-structured metacognition to Increase problem-solving ability belongs to a large 41%.